The Role of Routine Weekly Religious Studies in Increasing Social Solidarity Among Youth at the Al-Falah Jami' Mosque in Pragaan, Sumenep - Ulfatun Hasanah; Itaanis Tianah (Universtias Islam Negeri Madura, 2026)
Weekly religious study activities are one form of religious programs that function not only as a means of enhancing Islamic understanding but also as an effective medium for strengthening social solidarity among youth. This study aims to describe the implementation of weekly religious study activities, analyze their impact on improving social solidarity, and identify the supporting and inhibiting factors of these activities among the youth of Jami’ Al-Falah Mosque in Pragaan, Sumenep. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of the head of the mosque youth organization and five youth members. The results show that the weekly religious study activities are conducted regularly and systematically with a series of religious and social activities. These activities have a positive impact on enhancing social solidarity, which is reflected in indicators such as mutual cooperation, mutual assistance, cooperation, and brotherhood. Supporting factors include support from mosque administrators and parents, strong collective spirit among members, and a friendly and comfortable atmosphere during the activities. Meanwhile, inhibiting factors include members’ busy schedules, weather conditions, and transportation limitations. Overall, weekly religious study activities play a significant role as a religious and social development medium in strengthening social solidarity among mosque youth.